Challenges in Managing Metabolic Syndrome in Psoriasis: A Narrative Review of Pharmacological and Surgical Treatments - Bętkowska, Aleksandra; Dudek, Stanisław; Koziak, Weronika; Makieła, Michalina; Kornacka, Agata; Dudek, Wojciech; Szostak, Kamila; Makieła, Marta; Tomaka, Rafał; Worobiej, Daniel (Quality in Sport, 2025)
Introduction: Psoriasis is a chronic inflammatory disorder associated with multiple systemic comorbidities, most notably metabolic syndrome, which affects approximately one-third of individuals with the disease. Metabolic syndrome—characterized by obesity, insulin resistance, dyslipidemia, and hypertension—exacerbates systemic inflammation, further complicating disease management and treatment outcomes. Aim of Study: This review explores the multidisciplinary approach to managing metabolic syndrome in psoriasis, with a particular focus on pharmacological and surgical interventions. It examines the challenges associated with these treatments and their implications for therapeutic efficacy. Brief Description of the State of Knowledge: Psoriasis and metabolic syndrome share a complex, reciprocal relationship driven by chronic inflammation and metabolic dysregulation. While lifestyle modifications remain the cornerstone of management, many patients require additional pharmacological or surgical interventions. However, the presence of metabolic syndrome can alter the safety and effectiveness of systemic and biologic psoriasis therapies, underscoring the need for a personalized treatment approach. Conclusions: Effective management requires interdisciplinary collaboration. Pharmacological treatments should minimize metabolic risks, while bariatric surgery may benefit selected patient groups. Further studies are needed to optimize treatment strategies and improve outcomes.